Value Adding for Environmental Social and Governance Influenced Investment by Technological Innovation - Dr.D. Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advancements in technology are in rapid phase with the Information and Communication Technology (ICT) as a big driver of other sectors to be automated in a large context. The right to life for various non-human living organisms is denied forcefully by many of the side effects of these human technological advancements. This has led to lot of ethical awareness among many Governments as well as private or institutional investors to implicate Environmental, Social and Governance (ESG) based decisions in the fund management, so that the Corporate Structure of such business they invest does not violate the ESG based ethics. This conceptual paper stretches its objectives for comparing the existing ESG based criteria in developed countries with focus on strategic policy making for the Asian peers. This study examines the importance of ESG in investment related decisions as well as policy making; and describe current influencing status of ESG in various ways as well as to identify the benefits and concerns through ESG in Startups investment. This paper also describes the use of various technological advancements in effective implementation and utilization of ESG at both Policy making as well as investment decisions. This paper mainly focuses on the study of effective ESG based sustainable investment in the startup culture through relative technological advancements.